2006
DOI: 10.1086/501364
|View full text |Cite
|
Sign up to set email alerts
|

Renal Injury Is a Consistent Finding in Dutch Belted Rabbits Experimentally Infected with EnterohemorrhagicEscherichia coli

Abstract: Enterohemorrhagic Escherichia coli (EHEC) produces Shiga toxin (Stx) and causes renal disease in humans. Dutch Belted (DB) rabbits naturally infected with EHEC O153 develop hemolytic-uremic syndrome-like disease. The aims of this study were to experimentally reproduce O153-induced renal disease in DB rabbits and investigate bacterial and host factors involved in pathogenesis. The pathogenicity of E. coli O157:H7 was also investigated in rabbits. The stx1AB region of O153 was sequenced. By use of liquid chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 38 publications
2
39
0
Order By: Relevance
“…An important subclass of STEC is EHEC, which triggers the formation of AE lesions on the intestinal mucosa. Some rabbit and piglet models manifest both AE lesion formation and Stx-mediated disease (21,23,52,53,85), but no such model has yet been developed in conventional mice. We show here that C. rodentium lysogenized with λStx2dact, which produces a mucus-activatable Stx previously associated with severe disease in mice (59)(60)(61), provides a model that features prototypic AE lesions during intestinal colonization and Stx-mediated weight loss and death, recapitulating renal dysfunction observed in human HUS and murine toxin injection models (4,54).…”
Section: Discussionmentioning
confidence: 99%
“…An important subclass of STEC is EHEC, which triggers the formation of AE lesions on the intestinal mucosa. Some rabbit and piglet models manifest both AE lesion formation and Stx-mediated disease (21,23,52,53,85), but no such model has yet been developed in conventional mice. We show here that C. rodentium lysogenized with λStx2dact, which produces a mucus-activatable Stx previously associated with severe disease in mice (59)(60)(61), provides a model that features prototypic AE lesions during intestinal colonization and Stx-mediated weight loss and death, recapitulating renal dysfunction observed in human HUS and murine toxin injection models (4,54).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous animal models have been developed, including mice, rats, chickens, rabbits, cows, greyhounds, baboons, and macaques (141,(173)(174)(175)(176)(177)(178). Although these models do not fully replicate all aspects of the STEC infection in humans, they provide valuable insight into intestinal colonization, STEC pathogenesis, immune response, and efficacy of possible treatment regimens (179,180).…”
Section: Animal Modelsmentioning
confidence: 99%
“…For example, infection with strain RDEC-1, a well-described model of human EPEC infection (6), mimics a disease process seen in children with infectious gastroenteritis (45). Other recent studies have shown that Dutch Belted rabbits naturally or experimentally infected with EHEC strains exhibit bloody diarrhea and typhlocolitis, as well as nephropathy and renal thrombosis characteristic of the hemolytic-uremic syndrome (11,12,14).…”
mentioning
confidence: 99%